1991
DOI: 10.1007/bf01281270
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological wave functions for the massA=14 system and a consistent description of beta decay observables

Abstract: A set of phenomenological wave functions has been derived to describe the 14N ground state and the isospin triplet consisting of the 14C ground state, the first excited state of 14N at 2.313 MeV and the 140 ground state. Elastic and inelastic electron scattering form factors, the magnetic moment of the 14N ground state and the shape factors in the /~ -+ decay have been employed in a multiparameter fitting procedure to determine the amplitudes of the wave functions in L-S coupling. The inclusion of the beta dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The 14 C spectrum shape factor can be parametrized as C(E) = 1 + αE. In the experiments [46,47] the parameter α was measured to be α −1.0 ± 0.04 MeV −1 in good agreement with theoretical predictions of [48]. But in experiment [49] a value α −0.45 ± 0.04 MeV −1 was obtained, which is consistent with other theoretical calculations [50,51].…”
Section: C Spectrumsupporting
confidence: 83%
“…The 14 C spectrum shape factor can be parametrized as C(E) = 1 + αE. In the experiments [46,47] the parameter α was measured to be α −1.0 ± 0.04 MeV −1 in good agreement with theoretical predictions of [48]. But in experiment [49] a value α −0.45 ± 0.04 MeV −1 was obtained, which is consistent with other theoretical calculations [50,51].…”
Section: C Spectrumsupporting
confidence: 83%
“…As we discovered, the 14 C beta spectrum is known to deviate from a purely allowed shape, with several discrepant shape factors reported in the literature based on experiment and calculation (Sonntag et al, 1970; Genz et al, 1991; García and Brown, 1995; Alimonti et al, 1998; Kuzminov and Osetrova, 2000). We reanalyzed our data with six different sets of shape factor coefficients (including allowed) from the literature, input into MICELLE2 for efficiency calculations.…”
Section: Resultsmentioning
confidence: 71%
“…and the 3.95 MeV state of 14 N were characterized by angular momentum transfers L 2 and 0, respectively [6]. This idea was also investigated extensively by Genz et al [7], who extracted phenomenological wave functions which were capable of describing many (but not all) features of the A 14 multiplet simultaneously. García and Brown [8] found that by mixing the two lowest 1 states and adding 2@!…”
mentioning
confidence: 97%